Late postoperative complications and dysfunction of the stomatognathic system (SS) in patients after orthognathic surgery - Górska, Alicja; Gębska, Magdalena (Journal of Education, Health and Sport, 2020)
Introduction: Patients with maxillofacial and intraoral defects require orthognathic surgery to improve the appearance of the face and correct the occlusion. The number of orthognathic surgeries has been increasing in recent years. The motivation to undergo these surgeries is the possibility for patients to improve stomatognathic system functions i.e. chewing, swallowing and pronunciation, as well as aesthetic and psychosocial factors. Aim: The aim of the paper was to assess the occurrence of late postoperative complications and dysfunction of the stomatognathic system in patients after orthognathic surgeries such as Maxillary Lefort 1 Osteotomy and Bilateral Sagittal Split Osteotomy (BIMAX). Additionally, the paper emphasizes the necessity of quick activation of the stomatognathic system structures in patients after orthognathic surgeries in order to reduce the incidence of complications. Material and methods: The research was conducted with the help of the users of internet groups: "Progenia, mandibular prognathism, photos BEFORE and AFTER the operation :)" (in Polish: „Progenia, wysunięta szczęka, zdjęcia PRZED i PO operacji :)”) and "Suffering from progenia" („Progenicy”) as well as users of the Jawsurgeryforums.com online forum who have given their informed consent to participate in the survey. The analysis was carried out on a group of 92 people who underwent orthognathic surgery of Maxillary Lefort 1 Osteotomy and Bilateral Sagittal Split Osteotomy (BIMAX) type in the years 2004-2019. To assess the opinions of patients, a diagnostic questionnaire method was used, based on a proprietary electronic questionnaire, which consisted of three parts. The first part is metric, i.e.: age, gender and questions concerning the number of orthognathic surgeries performed, time of wearing intermaxillary traction wiring or splints, postoperative rehabilitation. The second part of the questionnaire consisted of 15 close-ended questions assessing the occurrence of symptoms of SS system disorders and functioning. The third part of the questionnaire consists of 20 questions concerning postoperative complications after 3 and 6 months from surgery and functioning of the dental system after surgery. The fourth part of the questionnaire consists of 5 close-ended questions concerning the evaluation of the overall impression after surgery and the most important effects of it. The test results were statistically analyzed using the correlation coefficient and Pearson's chi-squared test (p ≤ 0.05). Results: 92 people, of which 86 women (93.5%) and 6 men (6.5%), participated in the study. The most common ailments before the surgery—affecting more than half of the patients—were chewing impairment, speech defect, breathing problems and headaches. 3 months after the operation, facial neurosensory disturbances and facial swelling were the most frequent of the ailments reported by the patients (more than 70% of the respondents), limited jaw mobility, joint pains and chewing impairment were also frequent (more than 40%). 6 months after the surgery, the most frequent persisting ailments were facial neurosensory disturbances (> 60%), facial swelling and acoustic problems (> 30%), as well as pains of masticatory and mandibular muscles, headaches and limited joint mobility (> 20%). More than half of the patients (n=48) were satisfied with the surgery, the second largest group were patients delighted with the result (n=25). 4 people were dissatisfied and 3 very dissatisfied. 12 patients had difficulties in determining their satisfaction with the results of the surgery. 19 people (20.7%) did not report disturbances of somatosensory system in any of the facial areas, and among the patients experiencing ailments, 40 people (43.5%) reported problems in two areas, 27 people (29.3%) in one, 5 people (5.4%) in four and 1 person (1.1%) in three areas. In the 3rd month after the surgery it was observed that people who did not use physiotherapeutic treatment were 11.5% more likely to suffer from bone inflammation [X2(1)=4.359; p=0.037]. Two statistical tendencies were observed, suggesting that people using physiotherapy slightly less often showed limitations in mandibular mobility [by 17.6%; X2(1)=3.599; p=0.065] and by 4.7% less often experienced bone inflammation [X2(1)=1.238; p=0.076]. Conclusions: The most common postoperative complication is somatosensory system disturbance of the lower facial muscles. Orthognathic surgery contributes to the reduction of stomatognathic system ailments. Persons using physiotherapy suffer less frequently from bone inflammation and enjoy greater mobility of the temporomandibular joint.